Connexin43 and connexin47 alterations after neural precursor cells transplantation in experimental autoimmune encephalomyelitis. Issue 10 (27th April 2015) - Theotokis, Paschalis; Kleopa, Kleopas A.; Touloumi, Olga; Lagoudaki, Roza; Lourbopoulos, Athanasios; Nousiopoulou, Evangelia; Kesidou, Evangelia; Poulatsidou, Kyriaki‐Nepheli; Dardiotis, Efthimios; Hadjigeorgiou, Georgios; Karacostas, Dimitris; Cifuentes‐Diaz, Carmen; et al.
<x xml:space="preserve">Abstract</x> Exogenous transplanted neural precursor cells (NPCs) exhibit miscellaneous immune‐modulatory effects in models of autoimmune demyelination. However, the regional interactions of NPCs with the host brain tissue in remissive inflammatory events have not been adequately studied. In this study we used the chronic MOG‐induced Experimental Autoimmune Encephalomyelitis (EAE) model in C57BL/six mice. Based on previous data, we focused on neuropathology at Day 50 post‐induction (D50) and studied the expression of connexin43 (Cx43) and Cx47, two of the main glial gap junction (GJ) proteins, in relation to the intraventricular transplantation of GFP+NPCs and their integration with the host tissue. By D50, NPCs had migrated intraparenchymally and were found in the corpus callosum at the level of the lateral ventricles and hippocampus. The majority of GFP+ cells differentiated with simple or ramified processes expressing mainly markers of mature GLIA (GFAP and NogoA) and significantly less of precursor glial cells. GFP+NPCs expressed connexins and formed GJs around the hippocampus more than lateral ventricles. The presence of NPCs did not alter the increase in Cx43 GJ plaques at D50 EAE, but prevented the reduction of oligodendrocytic Cx47, increased the number of oligodendrocytes, local Cx47 levels and Cx47 GJ plaques per cell. These findings suggest that transplanted NPCs may have multiple effects in demyelinating pathology, including differentiation and direct integration into the panglial syncytium, as well as amelioration of oligodendrocyte GJ loss, increasing the supply of potent myelinating cells to the demyelinated tissue. GLIA 2015;63:1772–1783